2017
DOI: 10.1038/s41598-017-09554-x
|View full text |Cite|
|
Sign up to set email alerts
|

LSD1 modulates the non-canonical integrin β3 signaling pathway in non-small cell lung carcinoma cells

Abstract: The epigenetic writer lysine-specific demethylase 1 (LSD1) is aberrantly upregulated in many cancer types and its overexpression correlates with poor survival and tumor progression. In this study, we analysed LSD1 function in non-small cell lung cancer adenocarcinomas. Expression profiling of 182 cases of lung adenocarcinoma proved a significant correlation of LSD1 overexpression with lung adenocarcinoma progression and metastasis. KRAS-mutated lung cancer cell clones were stably silenced for LSD1 expression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…5B and C). In a previous study, we showed that LSD1 levels correlate with tumor grade in lung adenocarcinoma (26). As evident from Fig.…”
Section: Lsd1 and Plk1 Expression Positively Correlates At Mrna And Psupporting
confidence: 57%
See 2 more Smart Citations
“…5B and C). In a previous study, we showed that LSD1 levels correlate with tumor grade in lung adenocarcinoma (26). As evident from Fig.…”
Section: Lsd1 and Plk1 Expression Positively Correlates At Mrna And Psupporting
confidence: 57%
“…Previous work from our laboratory showed that LSD1 is overexpressed in lung adenocarcinomas and its expression correlates with tumor grade and invasive phenotypes (26). To identify the underlying molecular and cellular mechanisms associated with higher tumor cell proliferation in presence of LSD1, we investigated the impact of LSD1 inhibition in lung adenocarcinoma cells using the LSD1 inhibitor HCI-2509.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we demonstrated that the LSD1 inhibitor HCI-2509 inhibits LUAD cell growth in a dose-dependent manner in vitro and in vivo. Because overexpression of LSD1 was observed in many cancer types, including NSCLC, inhibition of LSD1 was suggested as a promising therapeutical option (Lv et al, 2012;Lim et al, 2017). Surprisingly, in contrast to treatment studies on acute myeloid leukemia and smallcell lung cancer (Mohammad et al, 2015;Stazi et al, 2016), conventional MAO-based LSD1 inhibitors neither affected the histone methylation status, nor influenced NSCLC cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…LSD1 is an epigenetic eraser that is drastically upregulated in various tumor types (Kahl et al, 2006;Schulte et al, 2009;Lim et al, 2010;Lin et al, 2011). In particular, LSD1 overexpression in NSCLC is associated with high malignancy and a poor prognosis (Lv et al, 2012;Lim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%